2018
DOI: 10.1155/2018/5302049
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture: A Feasible Sirt1 Promoter Which Modulates Metainflammation in Diet‐Induced Obesity Rats

Abstract: It is generally accepted that metainflammation, a state of chronic and low-grade inflammation in obesity, plays a great role in metabolic disorder like insulin resistance. To gain further insight into the mechanism of metainflammation and find feasible therapy of obesity, diet-induced obesity (DIO) rats model and Electroacupuncture (EA) treatment were established in this trail. The results indicated that rising Lee's index, hyperlipidemia, insulin resistance, and increasing inflammation factors including NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In comparison, dietary intervention has proved to be a healthy and effective way to lose weight, but it needs long-term persistence. Accumulating studies have indicated that electroacupuncture can treat abdominal obesity safely and effectively, mainly by stimulating the body’s meridians and acupoints, improving body condition as a whole, regulating intake and enhancing body metabolism, so as to achieve the purpose of weight loss and waist thinning ( Wang et al, 2008 ; Lei et al, 2017 ; Chen et al, 2018 ; Luo et al, 2018 ; Huang et al, 2019 ; Zhang et al, 2019 ). However, the effect mechanism of electroacupuncture on abdominal obesity in perimenopausal women is still dearth of in-depth exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, dietary intervention has proved to be a healthy and effective way to lose weight, but it needs long-term persistence. Accumulating studies have indicated that electroacupuncture can treat abdominal obesity safely and effectively, mainly by stimulating the body’s meridians and acupoints, improving body condition as a whole, regulating intake and enhancing body metabolism, so as to achieve the purpose of weight loss and waist thinning ( Wang et al, 2008 ; Lei et al, 2017 ; Chen et al, 2018 ; Luo et al, 2018 ; Huang et al, 2019 ; Zhang et al, 2019 ). However, the effect mechanism of electroacupuncture on abdominal obesity in perimenopausal women is still dearth of in-depth exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Most acupuncture or EA research studies using rodent models benefited from previously published studies for the acupoints localization [ 85 , 110 ] or adapted the definition of rodent acupoints on the basis of the human anatomical acupoints location [ 88 , 104 ]. To date, we found no clear and systematic description of rodent acupoints in the general and scientific literature [ 96 , 112 ], besides the fact that many acupoints cannot be identified in rodents because of significant anatomical differences compared to humans. Humans sleep and rest at night, which is consistent with the meridian work (circular motion) time dependent on the circadian rhythm, but rats and mice, as nocturnal species, normally exercised at night and sleep during daytime.…”
Section: Rodent Models Of Obesity and Acupuncture/electroacupuncturementioning
confidence: 99%
“…In anaesthetized minipigs, rather than relying on the individual’s feedback, we will look for objectifiable criteria, such as muscle contraction. This is the case in rats for example, where Luo et al [ 15 ] selected 2-Hz continuous wave for 10 min, with an intensity starting from 1 mA and progressively increasing until the induction of slight muscle contraction. In mice, Choowanthanapakorn et al [ 93 ] used 2-Hz frequency, 100-μs duration, with an intensity of 1 mA for 15 min, whereas Lim et al [ 69 ] selected 1-Hz frequency, 2-ms pulse duration, and 1-V voltage for 30 min.…”
Section: Toward a Preclinical Study In The Diet-induced Obese Minipigmentioning
confidence: 99%
“…In multiple clinical studies, significant outcomes of acupuncture or EA were found on the body mass index, weight loss, waist circumference, fat mass, total cholesterol, and plasma triglycerides [12]. Many researchers hypothesized that these therapeutic strategies modulate complex processes involving the gastrointestinal tract, related hormones, and the central and autonomic nervous systems [12,13], also inhibiting inflammatory signals [14][15][16]. EA consists in applying a slight electric stimulation to the acupuncture needles to potentiate the expected effects of acupuncture alone.…”
Section: Introductionmentioning
confidence: 99%